Evolution of public library architecture as based on the work of Alvar Aalto and the extension of the Seinäjoki library - Šlapeta, Vladimír; Gierbienis, Marcin (Wydawnictwo Politechniki Krakowskiej, 2024)
The paper discusses how library architecture has evolved over the centuries on the case study of the extension of the public library in Seinäjoki. Finnish city is also known for the work of Alvar Aalto, who created a civic centre that also became the site of one of the most interesting libraries. Aalto was passionate about this form of use, which accompanied him through various stages of his career. Given that the old building and the new one were built less than half a century apart, it is interesting from a research point of view to compare their architecture, aesthetics and approach to spatial organisation.

The paper discusses how library architecture has evolved over the centuries on the case study of the extension of the public library in Seinäjoki. Finnish city is also known for the work of Alvar Aalto, who created a civic centre that also became the site of one of the most interesting libraries. Aalto was passionate about this form of use, which accompanied him through various stages of his career. Given that the old building and the new one were built less than half a century apart, it is interesting from a research point of view to compare their architecture, aesthetics and approach to spatial organisation.
Evolution of public library architecture as based on the work of Alvar Aalto and the extension of the Seinäjoki library
Keywords: library; organic architecture; sustainable development; Alvar Aalto; library; organic architecture; sustainable development; Alvar Aalto